Penggunaan Media Berbasis Gambar Guna Meningkatkan Pemahaman Pengajaran PAK sekolah Minggu Usia Pratama di GKIN Ephata Wlingi - Sianturi, Juliana; Allfadiser, Thomas (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen, 2023)
The use of image-based media in teaching, is also needed as a means to teach in conveying material. Therefore, the use of image-based media is expected to be able to improve understanding of PAK teaching, especially in Sunday Schools of primary age. The purpose of this study is to find the reality, in the use of image-based media that is used as a medium to deliver PAK teaching in Sunday Schools. This research uses qualitative research with a case study approach. The research results obtained from the reality of using image-based media are to determine the material to be delivered. So, before the use of image-based media is used, the teacher first determines the material to be delivered, then the use of the media has a match with the material that has been determined.